A Literature-Based Exploration of Innovative Strategies to Improve English Language Skills in Higher Education - Fitria Dewi Navisa; Elfiyanto, Sonny; Wayne (IJORER : International Journal of Recent Educational Research, 2025)
.Objective: This study explores innovative teaching methods to enhance English language skills in higher education. Given the increasing significance of English in a globalized world, traditional teaching approaches often fail to meet student needs effectively. This research investigates strategies such as digital technology integration, project-based learning, gamification, blended learning, and collaboration-based approaches to improve student engagement and language proficiency. Method: A qualitative research approach was employed, utilizing literature analysis to examine various innovative teaching methods. Peer-reviewed journals, conference papers, and educational resources were analyzed to identify patterns, challenges, and best practices for implementing these strategies in English language education. Results: The study found that the use of digital tools, project-based learning, gamification, and blended learning significantly improved students' English skills. These methods encouraged active engagement, language accuracy, and self-directed learning. Successful implementation depends on lecturer readiness, institutional support, and access to technology. Novelty: This study presents a comprehensive analysis of innovative pedagogical approaches, emphasizing their effectiveness and the challenges they pose within higher education. It offers practical recommendations for educators and policymakers to enhance English language instruction by addressing both institutional and pedagogical barriers.